Expatriate teachers’ beliefs : working within a UAE federal community college. - Degazon, George A. (2019)
What are the beliefs of expatriate teachers who live and work in a foreign country?. The research identifies and interprets the beliefs of expatriate teachers working within a federally run, English-medium college in the United Arab Emirates providing free vocational education to local Emirati students. The period of the study was from 2009 - 2010. The study aimed to explore and understand their beliefs within the environment that affect expatriate teachers’ practice. An interpretative case study approach investigated ten expatriate teachers, (three English teachers and seven subject specialists) selected from a stratified sample employed within a vocational institution. Two semi-structured interviews were conducted, amounting to over 20 hours of recorded discussions. The political, social and cultural context was also documented through a literature review. A vocational community of practice initiative provided the opportunity to collect data for a preliminary study. Discussion from two group sessions and four individual interviews provided three broad themes to frame the research questions: • teaching and learning • their knowledge of Emirati students • their views on the organisation in which they work The key questions explored expatriate teachers’ perspectives about Emirati students and the organisational context in which they worked. Expatriate teachers were questioned on their understanding of the Emirati student approach to education, the Emirati student influence on the organisation and the cultural cues which affected their teaching. In addition, the study explored expatriate teachers’ perspectives on the organisational context in which they worked, the security of their employment and the issues affecting their morale. The investigation adds to the collective understanding of expatriate teachers’ perspectives and beliefs within a UAE Emirati cultural teaching context. The findings indicated that expatriate teacher beliefs are set within a political, social and employment context where the balance of power is with the employer and an employment landscape is governed through short-term employment contracts. Emirati student opinions obtained through regular feedback played an important role in teacher evaluations. The resulting insecure job context provided challenges for engagement, commitment and professional development. Expatriate teachers expressed concern about the impact of student-teacher evaluations, student influence, their job security and the power of their employer. In addition, expatriate teachers commented that student success was supported by a positive teacher/ student working relationship with strong social and cultural connections, thus nurturing a student-centric approach to teaching, which was both vocational and practical. There is a tension between raising standards and driving student achievement and the balance between failure and success, which could ultimately influence the job survival of the teacher within the institution. This research contends that institutions who engage expatriate teachers must acknowledge and mitigate the political, social and cultural context in order to ensure that the goals of achieving student success are realised. Engagement could be in the form of continuous professional development, which incorporates social and cultural training to support contextual effective teaching practice.